2015
DOI: 10.2174/1573397111666150522095321
|View full text |Cite
|
Sign up to set email alerts
|

The Peri-operative Management of the Rheumatoid Patient Undergoing Total Knee Arthroplasty: A Review of Literature

Abstract: Rheumatoid arthritis is the commonest inflammatory arthropathy, and affects synovium, cartilage and bone. Despite recent improvements with disease modifying biological agents, progressive joint destruction may continue eventually leading to the need for joint arthroplasty. The knee joint is involved in 90% of patients with rheumatoid arthritis, and total knee arthroplasty is being performed in many patients to alleviate pain and recover function. However, complications are not uncommon. In this review of the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Unpublished studies in the form of dissertations and theses were included to reduce publication bias (Trespidi, Barbui, & Cipriani, ). Studies were excluded if they (1) involved patients with trauma or rheumatoid arthritis as the conditions were known to differ in pathogenesis, prognosis, and management from OA (Krause & Matteson, ; Sohail, Anesti, Hanna, Khan, & Malik, ), (2) duplicated publications or publications using replicated patient data, and/or (3) secondary research and/or commentaries, editorials, expert opinions, and books. Uncertain cases were discussed with the second reviewer, A.J.Q.T., to achieve consensus for article inclusion.…”
Section: Review Methodsmentioning
confidence: 99%
“…Unpublished studies in the form of dissertations and theses were included to reduce publication bias (Trespidi, Barbui, & Cipriani, ). Studies were excluded if they (1) involved patients with trauma or rheumatoid arthritis as the conditions were known to differ in pathogenesis, prognosis, and management from OA (Krause & Matteson, ; Sohail, Anesti, Hanna, Khan, & Malik, ), (2) duplicated publications or publications using replicated patient data, and/or (3) secondary research and/or commentaries, editorials, expert opinions, and books. Uncertain cases were discussed with the second reviewer, A.J.Q.T., to achieve consensus for article inclusion.…”
Section: Review Methodsmentioning
confidence: 99%
“…All three of the TNF-α inhibiting agents: infliximab, adalimumab and etanercept have been shown to cause pancytopenia. These drugs may contribute to postoperative complications or poor wound healing and infection (Sohail et al 2015). There is, however, conflicting evidence on this topic (Sohail et al 2015).…”
Section: Preoperative Evaluationmentioning
confidence: 99%
“…These drugs may contribute to postoperative complications or poor wound healing and infection (Sohail et al 2015). There is, however, conflicting evidence on this topic (Sohail et al 2015). A literature review covering the discussion of stopping TNF-α inhibiting medication before elective orthopaedic surgeries has shown that data from the national registries of rheumatoid arthritis patients illustrate that there is an increased risk of infection in these patients on TNF-α inhibitors (Goh et al 2012).…”
Section: Preoperative Evaluationmentioning
confidence: 99%
“…During endoprosthetic repair of knee joints, complications are usually due to careless planning of the surgical intervention, fracture of the femoral and tibial condyles [10]. It should be taken into account that the density of bone tissue is lower in patients with RA due to the immunosuppressive effect of long-term use of steroids, the level of prostaglandins in the synovial fluid or the presence of rheumatoid granulation tissues among the cancellous bone tissue [11], which has a significant impact on the risk of complications after total knee arthroplasty. They can include such undesirable conditions as infection (early or late, superficial or deep), migration of the structure, peri-articular fractures, hematomas, neuritis, thromboembolism, wear and tear of polyethylene.…”
Section: Introductionmentioning
confidence: 99%
“…The main factors in the development of complications, according to the majority of orthopedists, are complex techniques of interventions, previous operations on the knee joint, insufficient management of patients in the postoperative period [11].…”
Section: Introductionmentioning
confidence: 99%